The Linguistic Resources of Tropes in the Media Construction of Anti-Graft Campaign in Nigeria (2015-2022) - Okugbe, Monday; Ambrose, Lynda Chinenye (Universitas Ahmad Dahlan, 2025)
The major hindrance causing underdevelopment in African countries, including Nigeria is corruption, and the role of the media in combating the menace is crucial. Therefore, this study examines the manner in which tropes in media reports shape public knowledge and perception of graft, with a view to fighting corruption through the writers’ presentation of anti-graft campaign within the Nigerian context. Data in the study comprise headline news, top stories, news and opinion articles which represent online version of the newspapers and news report Journals. The publications represent the media presentation on graft and anti-graft campaign in Nigeria which fall within the period of 2015 to 2022. The study uses descriptive, interpretative, and explanatory methods to analyze language patterns in the data. It applies conceptual metaphor theory to examine how media reports frame corruption. Findings show that the use of tropes in anti-graft campaigns helps engage the public, making them more receptive to critical and rational media reports that address corruption from different perspectives.